(3GdefM GdecjI aj TQM GdgeRjIs - (3CMeO Hf eMeO Hf Ydj Hf nMnLQ GdngrjnJej GdSYOj GdCfUGQj, TgGH GdOjf TjN GdESdGe, CHh GdYHGS,J (B974 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi GNJU fHjfkG eMeOkG (B((3U(B) (3HcJGH CNQS GdaUMGA , hGYLR GdHZGA Yf GdJahg HeKd CbUQ ShQI ef ShQg s
(3BNQgG (B:s
(3hHGdKGfi GdPi dGjfbWY dOhGe fYje GdLfI hYPGH GdfGQ djLeY Hjf TQa GdChd hOhGe GdKGfi s
(3HgG fXGe GdJYbjHIs
(3hgh TQM Ydi GdbUjOg GdgeRjg ai GdeOGFM GdfHhjg ddHhUjQi hGdJi JSei Ce GdbQis
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B234 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B152s
Keywords: (3GdCOHs